2014
DOI: 10.1158/1535-7163.mct-12-0767
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Small-Molecule Inhibitor of Mcl-1 Blocks Pancreatic Cancer Growth In Vitro and In Vivo

Abstract: Using a high throughput screening (HTS) approach, we have identified and validated several small molecule Mcl-1 inhibitors (SMIs). Here we describe a novel selective Mcl-1 SMI inhibitor, 2 (UMI-77), developed by structure-based chemical modifications of the lead compound 1 (UMI-59). We have characterized the binding of UMI-77 to Mcl-1 by using complementary biochemical, biophysical and computational methods, and determined its antitumor activity against panel of pancreatic cancer (PC) cells and in vivo xenogra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
172
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 170 publications
(176 citation statements)
references
References 40 publications
4
172
0
Order By: Relevance
“…5 MCL-1 protein levels correlate with outcome, tumor grade and therapeutic resistance in many cancers including those of the hematopoietic system, breast, lung and pancreas. [6][7][8][9][10][11][12] MCL-1 has been validated to participate in neoplastic progression of B-cell lymphomas 13 as well as haematopoietic progenitor/stem cell tumours 14 and accelerate Myc induced myeloid leukaemia. 15 Several studies have also shown that MCL-1 is a barrier to therapeutic sensitivity, including those that target BCL-2 (reviewed in 16 ).…”
Section: Mcl-1 Is Important For Cancer Cell Survival and Therapeutic mentioning
confidence: 99%
“…5 MCL-1 protein levels correlate with outcome, tumor grade and therapeutic resistance in many cancers including those of the hematopoietic system, breast, lung and pancreas. [6][7][8][9][10][11][12] MCL-1 has been validated to participate in neoplastic progression of B-cell lymphomas 13 as well as haematopoietic progenitor/stem cell tumours 14 and accelerate Myc induced myeloid leukaemia. 15 Several studies have also shown that MCL-1 is a barrier to therapeutic sensitivity, including those that target BCL-2 (reviewed in 16 ).…”
Section: Mcl-1 Is Important For Cancer Cell Survival and Therapeutic mentioning
confidence: 99%
“…[17] Thed eployment of the NoxaB peptide as as caffold for discovering new compounds was envisaged to also impart this selectivity onto the new small-molecule mimics.T oexamine this,weemployed two in vitro FA assays with Bcl-2 and Bcl-x L ,u sing an FITC-tagged Bid peptide as our fluorescent marker. [22] Navitoclax (ABT-263) was employed as apositive control and as an additional indication that the FA assay was performing adequately.…”
Section: Protein-proteininteractions(ppis)regulatemanyprocessesmentioning
confidence: 99%
“…MCL-1 UMI-77 inhibits proliferation of pancreatic cancer cells and induces intrinsic apoptotic pathways [70].…”
Section: Umi-77 [70]mentioning
confidence: 99%